Understanding Inclusion and Participation of People From Black African Diaspora Communities in Health and Care Research: A Realist Review - Eleanor Hoverd; Sophie Staniszewska; Jeremy Dale; Dawn Edge; Rachel Spencer; Violet Effiom; Dionne Gravesande; Lorna Hollowood; Samantha Johnson; Tony Kelly; Roy McFarlane; Esther Mukuka; et al. (Health Expectations, 2025)
ABSTRACT Background People from Black African Diaspora Communities (BAFDC) experience poorer health outcomes and are persistently under‐represented in health and care research. There is limited understanding about how to support their greater inclusion and participation. Objectives Explore secondary data providing insights for the co‐development of a realist theory of inclusion and participation for people from BAFDC in health and care research in the United Kingdom. Drawing on these theories, co‐produce a realist review with a diverse range of people from BAFDC. Methods A realist approach underpinned the study. Pawson's five steps to a realist approach were taken to shape the review, identify relevant sources, extract the data and then analyse and synthesise to inform an overarching programme theory. Initial programme theories (IPTs) were developed through context (C), mechanism (M), outcome (O) configurations (CMOCs). Main Results The review identified 43 relevant documents. Synthesis of evidence from the documents resulted in 8 IPTs and 17 CMOCs helping to understand and explain the inclusion and participation of people from BAFDC. Four key thematic clusters emerged: (1) Health and care research as a White space, (2) Trust deficit: the expansiveness of broken trust, (3) Implicit and complicit bias and (4) Processes that affect inclusion and participation. Findings were underpinned by five existing mid‐range theories (MRTs) around central concepts of candidacy, social dominance, networks, narratives and racism that guided analysis and synthesis, supporting conceptualisation of CMOCs. An overarching programme theory was developed. Conclusion The review identifies how the influence of perspectives, attitudes and beliefs held by individuals or groups about people from BAFDC operates in health and care research, resulting in exclusion, lack of trust and deficit thinking. The findings should be used to inform interventions aimed at increasing inclusion and participation of people from BAFDC. Patient or Public Contribution The co‐production group comprised a diverse range of individuals from within the health and care research system with different lived experiences of being Black. They contributed to the entire review process, including the development of initial programme theories and retroductive thinking and interpretation of the evidence. Clinical Trial Registration Not applicable.